Onomasticon Ottomanicum : identification administrative et désignation sociale dans l’État ottoman du xixe siècle - Olivier Bouquet (Revue des Mondes Musulmans et de la Méditerranée)
From a corpus of 282 pashas taken from the collection of sicill-i ahval compiled under the reign of Sultan Abdul Hamid II (1876-1909), this article proposes a reflection on the methods of attribution and the uses of names at the end of the Ottoman period. It first presents the main structures of the name (ism, mahlas, lakab) and the ways dignitaries use them in order to comply with the identification procedures used by the Ottoman administration. The article then attempts to show that the official name given in the biographies is not always the same as the dignitary's social name, the name used in pursuit of his daily activities, or the name given at birth. The individual's user name was often changed (school, geographical relocation, professional or cultural environment). Moreover, not only did many Ottomans await their first beard before taking an adult name, but the use of a personal name was varying considerably according to the context in which they received their name. As a result, administrative identification only reflects a part of the individual's onomastic identity: names should be studied as historical categories rather than as "rigid identifiers".